Особливості управління державним боргом та методи його удосконалення - Вівчар, О. Й.; Солдак, М. Ю. (Видавництво Львівської політехніки, 2011)
Висвітлено сутність державного боргу України, здійснено його аналіз, вказані наслідки, які має його динаміка на економіку країни і подано пропозиції щодо підвищення ефективності політики управління державним боргом. Essence of national debt of Ukraine is reflecte in the article, his analysis, indicated consequences which his dynamics has on the economy of country and suggestions are given in relation to the increase of efficiency of policy of management a national debt, is carried out.
Feature of management national debt and methods of his improvement
Keywords: державний борг; управління державним боргом; боргова безпека; боргова стратегія; national debt; management; promissory safety; promissory strategy; a national debt